2015
DOI: 10.1890/es14-00326.1
|View full text |Cite
|
Sign up to set email alerts
|

Reed Parrotbill nest predation by tidal mudflat crabs: Evidence for an ecological trap?

Abstract: Abstract. Understanding the relationships between nesting habitat quality and predation risk is essential for developing appropriate conservation management for threatened species. This is particularly relevant where anthropogenic pressures could decouple the environmental cues used by birds to assess nesting habitat quality from increased predation risk. In this study, we conducted a series of surveys and nest experiments to examine the nest predation rates of Reed Parrotbill (Paradoxornis heudei ) a passerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…We carried out the fieldwork from May to August in 2008 (parrotbills only) and in 2010-2012 (warblers and parrotbills) in the YRD National Nature Reserve (37°35′−38°12′ N, 118°33′−119°20′ E), Shandong, Eastern China. The study area is located in the second largest estuarine wetland area of China and contains extensive reed habitats, interspersed with stretches of black locust Robinia pseudoacacia forests and farmlands (see Li et al 2015a for more details). Warblers are recognized as the main hosts of the cuckoo in lowland reed habitats of Eastern Asia (Yang et al 2012(Yang et al , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…We carried out the fieldwork from May to August in 2008 (parrotbills only) and in 2010-2012 (warblers and parrotbills) in the YRD National Nature Reserve (37°35′−38°12′ N, 118°33′−119°20′ E), Shandong, Eastern China. The study area is located in the second largest estuarine wetland area of China and contains extensive reed habitats, interspersed with stretches of black locust Robinia pseudoacacia forests and farmlands (see Li et al 2015a for more details). Warblers are recognized as the main hosts of the cuckoo in lowland reed habitats of Eastern Asia (Yang et al 2012(Yang et al , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The high levels of predation by mammals within the PA, despite optimal nest site selection, may also represent an ecological trap for the plovers (Donovan & Thompson, 2001). This is, in fact, not uncommon in many other protected area ecosystems (Li et al, 2015), and disentangling the drivers of this potential ecological trap, such as the high nest predation rate by mammals within the protected area, would be a crucial first step to improve PA conservation management further. In the recently restored sparse vegetated and bare land that was sampled for this study, we have only found fewer than 10 nests of Saunders's gulls and other tern species within the colony of Kentish plovers, which perhaps implies that there were fewer benefits from any collective defense by these species against mammal predators.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the consequences of ecological traps for species conservation within modified habitat (e.g. agricultural fields, airports, reservoirs and urban areas (Gates and Gysel 1978, Best 1986, Marini et al 1995, Li et al 2015). Yet oil wells have received relatively less attention as a potential ecological trap for wild species in disturbed landscapes (Ludlow and Davis 2018).…”
mentioning
confidence: 99%